(untitled) (Sains Humanika, 2018)
Graduates’ employability plays a significant role in justifying the effectiveness of the technical and vocational education system (TVE). This issue has been debated among scholars for a long time and this concept has gained significant attention from organizational administrators as well as academicians. This study aims to understand more deeply about the dimensions of graduates’ employability skills and it impact on graduates as workers and organizations. In-depth study has been carried out by analysing previous literature related to TVE, graduates’ employability skills and training and development. This study incorporates a number of skills dimensions that are able to develop robust employability skills among graduates such as skill applications, self-efficacy, metacognition, entrepreneurial skills and soft skills. In this regard, it is a priority for the TVE system to equip graduates with the ability to apply skills, enhance self-efficacy skills, metacognition, entrepreneurial skills and soft skills so that graduates have the skills required by the organization to enhance graduates’ employability. This study also summarizes the dimensions of employability skills from the perspective of the organization and TVE through the development of a model of graduates’ employability. This model can be used by organizations and TVEs to identify and define key skills in graduates’ employability skills.